Programmes optimaux d’investissement en R & D - Nguyen, The-Hiep (L'Actualité économique, 1980)
AbstractThis article presents a model of inventive activity and capital accumulation. It also suggests ways of estimating optimal investment in research and development and outlines in the same time some econometric problems associated to measurement. In such a model, it has been shown that increases in technical knowledge are fundamentally related to the amount of resources devoted to inventive activity. Thus the role of invention in economic growth is explicitly recognized